The Effect of Social Networks on Freshmen Students of the Education Faculty: A Comparative Study of the 2016 and 2022 Academic Year - Hannah K. Surji; Aivar L. Surji (International Journal of Social Sciences & Educational Studies, 2024)
The popularity of social networks has reached remarkable heights with users spending extensive time using them. Social networks have become a firm part of society especially in the lives of learners. Changes can be seen throughout the years regarding interest and usage of social networks. Accordingly, this study’s objectives concentrate on the exploration and comparison of freshmen students’ social network usage from the academic years of 2016 and 2022 in the Faculty of Education at Tishk International University. Further, the freshmen respondents were given the same quantitative questionnaire. The data disclosed the social network that was most favored, the device used to access social networks, their perception regarding the effective communicational format, its influence on grades, and difference amid learners considering a temporary social media hiatus from these academic years. Therefore, this study indicated that the freshmen contributors of the academic years of 2016 and 2022 regarded and handled social networks differently.